(untitled) (Journal of Advanced Research in Social Sciences, 2025)
Transparent terms are words that share the same spelling and the same meaning in different languages, such as: robot, hotel, zoo… All those words are the same both in French and English for example. Those words seem to be easy to translate both ways; However, some terms don’t apply to this rule, which are scientific terminology. In mathematics, ‘natural numbers’ in English refers to all the positive numbers starting from 1 to infinity, but in French, the set of ‘nombres naturels’ also includes 0. This example shows two terms that are similar in spelling but different in meaning, which may lead to a wrong translation if the translator doesn’t have a scientific background. Transparent terms are not reliable in scientific translation; translators should always know exactly the meaning of every term. Moreover, bilingual readers and scientists should be careful and never assume the meaning of these words based on their similarity, especially in exact sciences. This paper explores the different types of transparent words and the pitfalls of assuming their meaning based on their similarities, It also includes some difficulties and strategies of their translation.